Influence Green Energy Awareness and Price Perception Towards Customer Satisfaction with the Decision to use Renewable Energy as an Intervening Variable (A Study on the Environment of PT PLN UP3 North Banten) - Fajar, Romi Anugerah; Tjahjaningsih, Endang (Dinasti Publisher, 2025)
The global reliance on fossil fuels has been proven to accelerate the pace of global warming, making the transition to renewable energy and the implementation of energy efficiency measures an urgent necessity. This study aims to analyze the influence of Green Energy Awareness and Price Perception on Customer Satisfaction, with the Decision to Use Renewable Energy as an intervening variable among medium and high-voltage customers within the operational area of PT PLN UP3 Banten Utara. A quantitative approach was employed by collecting primary data through questionnaires distributed to 100 respondents using a non-probability sampling technique. The data were analyzed using multiple linear regression and the Sobel test to examine the mediating effect. The findings indicate that both Green Energy Awareness and Price Perception have a positive influence on the decision to use renewable energy. Furthermore, Green Energy Awareness, Price Perception, and the Decision to Use Renewable Energy all positively influence Customer Satisfaction. The decision to use renewable energy mediates the effect of Green Energy Awareness and Price Perception on Customer Satisfaction. These findings provide valuable insights for the development of renewable energy initiatives in Indonesia.